TYPES OF METHODS USED IN ELEMENTARY READING LESSONS (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2024)
The types of oral methods, instructional methods, and practical methods used in elementary school reading lessons are discussed